A Contribution to the Biodiversity of Charekh Ka Danda and its Adjacent Area in District Pauri Garhwal of Uttrakhand (India) - Ghildiyal, J. C.; Bebni, Prabhakar Chandra (Indian Forester, 2010)
Charekh ka Danda lies in Matiyali Range of Lansdowne forest division, situated in Dugadda Block of District Pauri Garhwal in Uttarakhand (India) and is situated between 29° 47' 36.49" to 29° 50'15.12" North latitude and 78° 28' 07.67" to 78° 33'32" East Longitude, at an altitude of 800m -1803m in outer Himalaya. An extensive study of the area yielded 601 plant species belonging to 145 families and 440 genera in a round the year collection. Out of the total species recorded. 453 were dicotyledons, 77 monocotyledons, 41 bryophytes, 28 pteridophytes and 02 gymnosperms. In the present study, the dominant family with 46 species was Leguminosae (sensu lato) whereas, the dominant genera were Ficus and Euphorbia with 10 and 8 species respectively. Other co-dominant families of the area are Poaceae (30), Asteraceae (29), Euphorbiaceae (20), Lamiaceae (19), Acanthaceae (18), Moraceae (14), Rubiaceae (14), Amaranthaceae (13) and Rosaceae (12). Monocot - Dicot ratio of this region is 1: 5.88 and species genera ratio is 1: 1.37.The area is rich in its faunal diversity also.